1988
DOI: 10.1902/jop.1988.59.5.301
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiologic Effects of Local Tetracycline Irrigation on Periodontitis

Abstract: This investigation was conducted on seven individuals referred for treatment of moderate adult periodontitis. Twenty-eight sites with an average probing depth of 5.6 +/- 0.9 mm were evaluated. One tooth per jaw quadrant was randomly assigned to receive one of the following treatments: (I) no treatment, i.e., control; (II) saline irrigation; (III) tetracycline irrigation and (IV) scaling and root planing (SC/RP). A plaque control program was instituted one week prior to the experimental period and reinforced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…The present findings are in accordance with previous studies that have shown the same significant effect of tetracyclines on subgingival microbial flora mornhoSince spirochetes and motile rods are considered to have important roles in the pathogenesis of periodontal disease [6,8,16,23], the decrease in the percentages of these microorganisms in the subgingival microbial flora from periodontally diseased pockets would have important implications for periodontal treatment. Therefore, it can be suggested that doxycycline has a signigicant effect on the morphotypes of pathological bacteria associated with periodontal disease, and it can be recommended as an adjunct to traditional periodontal therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings are in accordance with previous studies that have shown the same significant effect of tetracyclines on subgingival microbial flora mornhoSince spirochetes and motile rods are considered to have important roles in the pathogenesis of periodontal disease [6,8,16,23], the decrease in the percentages of these microorganisms in the subgingival microbial flora from periodontally diseased pockets would have important implications for periodontal treatment. Therefore, it can be suggested that doxycycline has a signigicant effect on the morphotypes of pathological bacteria associated with periodontal disease, and it can be recommended as an adjunct to traditional periodontal therapy.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, extensive studies have been conducted with metranidazole and tetracyclines [7,[9][10][11][12]22,23]. Due to their high concentration in gingival crevicular fluid, their ability to bind to bone and inhibit tissue collagenase, tetracyclines are the most recommended group of antibiotics for treatment of periodontal disease [13,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the percentages of motiles and the increase in the percentages of cocci were highly significant in the treatment groups compared with the control group. Fig.2 Rate of release ( ƒÊg/h) of DOXY and CHx from HPMC membranes Table 1 Summary of the statistical differences between all the groups at each visit for the measurement parameters determined by analysis of variance Table 2 Mean and standard deviation of pocket depth in the treatment and control groups at the baseline (Visit 0) and for each visit up to 10 w (Visit 4) Table 3 Mean and standard deviation of gingival shrinkage for the treatment and control groups at the baseline (Visit 0) and at each visit up to 10 w (Visit 4) Table 4 Mean and standard deviation of the bleeding score for the treatment and control groups at the baseline (Visit 0) and at each visit up to 10 w (Visit 4) Table 5 Mean and standard deviation of crevicular fluid flow in the treatment and control groups at the baseline (Visit 0) and at each visit up to 10 w (Visit 4) Table 6 Mean and standard deviation of the percentage of curved and motile rods and spirochaetes in the treatment and control groups at the baseline (Visit 0) and at each visit up to 10 w (Visit 4) [24][25][26] and concentration in crevicular fluidi [11] , but also their fibroblast-stimulating activity [27,28] , enhancement of bone regeneration [29][30][31] , substantivity to mineralized tissues [32], and anticollagenolytic activity [33,34].…”
mentioning
confidence: 99%
“…Silverstein et al 46 reported on the effects of professional irrigation using a Hamilton syringe containing 5 mg/ ml tetracycline hydrochloride on untreated periodontal pockets when used every 48 hours for 2 weeks. Eight weeks posttreatment, the changes observed in subgingival microflora and clinicial indices were similar to those observed following scaling and root planing alone.…”
Section: Penetrability Of the Irrigantmentioning
confidence: 99%